Augmentations to the asset-based community development model to target power systems. (2nd January 2023) - Maclure, Liam
ABSTRACT: The asset-based community development (ABCD) approach has been criticized for neglecting external power systems' influence on local communities. To understand ABCD's theoretical engagement with power, this article uses a power framework from Gaventas' PowerCube'). The analysis illuminates how ABCD engages with four specific types of power: "power with, " "power over, " "power to, " and "power within." I then discuss the "dark side" of ABCD, namely the consequences for communities resulting from ABCD's neglect of power systems. Drawing on anti-oppression theory and Freire's emancipatory pedagogy, I propose augmentations to the ABCD model to resolve those shortcomings and directly target oppressive power systems. A three-part augmented model is presented that maintains consistency with the original ABCD process.